2016
DOI: 10.1038/ng.3568
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer risk variant in LINC00673 creates a miR-1231 binding site and interferes with PTPN11 degradation

Abstract: Genome-wide association studies have identified several loci associated with pancreatic cancer risk; however, the mechanisms by which genetic factors influence the development of sporadic pancreatic cancer remain largely unknown. Here, by using genome-wide association analysis and functional characterization, we identify a long intergenic noncoding RNA (lincRNA), LINC00673, as a potential tumor suppressor whose germline variation is associated with pancreatic cancer risk. LINC00673 is able to reinforce the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
219
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(226 citation statements)
references
References 66 publications
6
219
1
Order By: Relevance
“…This association subsequently replicated in a Han Chinese population (rs11655237, OR = 1.26, P = 3.95×10 −14 ) 161 . Through its epigenetic regulation of gene expression, LINC00673 may function as an oncogene in several types of cancers.…”
Section: Common Low-risk Susceptibility Locimentioning
confidence: 72%
See 1 more Smart Citation
“…This association subsequently replicated in a Han Chinese population (rs11655237, OR = 1.26, P = 3.95×10 −14 ) 161 . Through its epigenetic regulation of gene expression, LINC00673 may function as an oncogene in several types of cancers.…”
Section: Common Low-risk Susceptibility Locimentioning
confidence: 72%
“…In contrast, expression of LINC00673 was significantly lower in PDAC cancer cells than in normal cells and tissues and overexpression of LINC00673 in the PDAC cell line substantially reduced the rate of cell proliferation. It was found that the single-nucleotide change at rs11655237 creates a miR-1231 binding site, which diminishes the effect of LINC00673 in an allele-specific manner and thus confer susceptibility to pancreatic tumorigenesis 161 .…”
Section: Common Low-risk Susceptibility Locimentioning
confidence: 99%
“…However, a recent study on pancreatic cancer revealed significantly lower expression of linc00673 in cancerous cells and tissues. Further, linc00673 reportedly acted as a tumor suppressor through regulation of the protein tyrosine phosphatase PTPN1 [21]. LncRNA SPRY4 intronic transcript 1 (SPRY4-IT1) was previously reported to be upregulated in melanoma cells., whereafter, Sun et al found that SPRY4-IT1 expression was downregulated and correlated with a poor prognosis of NSCLC [22].…”
Section: Discussionmentioning
confidence: 99%
“…They found that the rs1899663 T allele was associated with BPH risk and the rs12826786 T allele was associated with both BPH and prostate cancer susceptibility. Even though the mechanisms underlying these two SNPs and HOTAIR are still unclear, we might find some clues from other non-coding RNAs such as the pancreatic cancer-associated long intergenic noncoding RNA lincRNA LINC00673 [61]. As shown in Figure 1A, LINC00673 is a tumor suppressor and can increase the interaction between PTPN11 and an E3 ubiquitin ligase PRPF19.…”
Section: Regulatory Mechanisms Underlying Risk Snps and Lncrnas Inmentioning
confidence: 99%